RETRACTED: Design and validation of ultra-compact metamaterial-based biosensor for non-invasive cervical cancer diagnosis in terahertz regime - Musa N. Hamza; Mohammad Tariqul Islam; Sunil Lavadiya; Iftikhar ud Din; Bruno Sanches; Slawomir Koziel; Md. Shabiul Islam (PLoS ONE, 2025)
Cervical cancer belongs to the most dangerous types of cancers posing considerable threat to women’s survival. It is most often diagnosed in the advanced stages as precancerous lesions are often symptom-free and difficult to identify. Microwave imaging, especially in terahertz (THz) range, is a convenient and noninvasive cancer detection tool. It enables characterization of biological tissues and discrimination between healthy and malignant ones. This study presents a novel triple-band biosensor based on metamaterials (MTMs). By leveraging unique properties of MTMs, the proposed biosensor operates as a perfect absorber. It exploits resonant modes in the THz spectrum to achieve remarkable sensitivity. Meticulous selection of the sensor geometry and dimensions enables efficient miniaturization. Meanwhile, utilization of frequency-domain data to detect refractive index changes improves resolution of cancerous tissue identification. Extensive numerical investigations corroborate its ability to carry out reliable early-stage cervical cancer diagnosis. This includes identification of the spatial extent of the malignant tissue. Excellent electrical properties of the sensor are accompanied by its compact size, which is highly desirable for non-invasive and portable applications.